Consumer Insurance Fraud/Abuse as Co-creation and Co-responsibility: A New Paradigm - Lesch, William C.; Brinkmann, Johannes (2011)
Insurance fraud and abuse—international concerns—are inherent in the proposition of insurance and prevalent in insurer–insured interactions. While the subject of considerable industry and regulatory attention, this little-researched area of consumer behavior and consumer ethics represents persistent social policy questions and problems at multiple levels. This article addresses the issue by first defining insurance fraud and its origins in contract, as well as consumer- and insurer-management. The authors conclude by re-envisioning the problem as one of co-creation by the consumer-insured and insurer personnel, proposing a framework for its study and resolution.
Keywords: Co-responsibility; Co-creation; Insurance abuse; insurance fraud